Penalaran Induktif dan Perumusan al-Maqosid Syatibi Menuju Ijtihad yang Dinamis - Asmuni M. Th (Unisia, 2003)
Traditionally, the theory of unrestricted interests (mashlahah) was derived into five aspects: it is close to the concept of al-maqashid al-syar'iyyah. Due to the inclusion of good ethics (makarim al-akhlaq) into mashlahah, then this needs to be reformulated intosome alternative concepts of mashlahah. There are interests for life (al-mashalih al-hayawiyyah), interests for brain (al-mashalih ai-aqliyah), and interests for soul (al-mashalih al-ruhiyah). The expected result Is, there will be an integrated concept of mahslahah.